NARMA-L2 Controller for Single Link Manipulator - Celikel, Resat; Aydogmus, Omur (Ieee, 2018)
All robotic systems require operating with minimum position error. The single link manipulator used in robotic applications is a nonlinear system for control algorithms. In this study, a single link manipulator system consists of dc motor, reducer gearbox and robot arm is controlled by using a modern control method known as NARMA-L2 controller. The system is analyzed via MATLAB / Simulink environment for various reference position angles. The load torque of the manipulator is taken into consideration by reducing to the motor side due to the gear ratio conversion ratio. The results show that the reference position angle is tracked by having a low error. In this work, satisfactory results are obtained by using NARMA-L2 controller for a single link manipulator.
International Conference on Artificial Intelligence and Data Processing (IDAP) -- SEP 28-30, 2018 -- Inonu Univ, Malatya, TURKEY
Keywords: Neural networks; NARMA-L2 controller; robot arm; DC motor